Increased Pulmonary Complications Associated with Intramedullary Fixation of Intertrochanteric Fractures: An Analysis of 13, 276 Hips. Issue 18 (15th September 2019) - Heckmann, Nathanael; Hill, J. Ryan; Vakhshori, Venus; McKnight, Braden; Mostofi, Amir; Davis, Jason; Hatch, George "Rick"; Marecek, Geoffrey
Abstract : Introduction: Intramedullary devices are being used more frequently to treat intertrochanteric (IT) femur fractures but without clear benefit in several clinical trials. This study determines differences in complication rates in patients with IT fractures treated with intramedullary versus extramedullary devices. Methods: Using the National Surgical Quality Improvement Program database, patients aged ≥55 years with an isolated IT fracture and an American Society of Anesthesiologists score of <5 were identified. Thirty-day mortality and perioperative complications were assessed. Results: Extramedullary fixation was performed in 4, 392 patients, whereas 8, 884 underwent intramedullary fixation. Intramedullary fixation was associated with increased 30-day mortality (odds ratio [OR], 1.18; P = 0.038), ventilator use (OR, 1.57; P = 0.004), transfusion (OR, 1.12; P < 0.001), and deep vein thrombosis (DVT) (OR, 1.45; P = 0.032). Mean postoperative hospital stay was 1 day shorter for the intramedullary group ( P < 0.001). After multivariate analysis, ventilator use (OR, 1.59), DVT (OR, 1.44), and transfusion (OR, 1.15) were more common with intramedullary fixation group. Discussion: Intramedullary fixation for IT fractures was associated with an increased risk of pulmonary complications, DVT, and transfusion. Further randomized controlled studies are required to determine the relative safety of intramedullary versus extramedullary implants. Level of Evidence: Level III, therapeutic, retrospective comparative study